Veri Madenciliği: İlahiyat Fakültesi Öğrencilerinde Akademik Başarının Veri Madenciliği İle Ölçülmesi - Baltacı, Ali (Muş Alparslan Üniversitesi, 2018)
This study; is designed as a theoretical review to determine thefoundations of data mining concept and its application areas. The study alsoincludes a sample application aimed at explaining what factors are influencingthe subsequent academic success of the students who have settled in the facultyof divinity, according to settling scores and various demographic variables.The relationship between the settling scores of the students settled in the facultyof divinity and their successes was determined from the data mining techniqueby quantitative research methods. In this study, 3775 students, who settled ina faculty of divinity in 2017 and are currently studying in the second year ofundergraduate programs, were sampled. As a result of the study, there was anegative correlation between the grade point average and the number ofunsuccessful courses. In addition, there was a high negative correlationbetween grade point averages and age at the end of the year. In addition, therewas a high negative correlation between grade point averages and age. The score of the student's placement in the universityaffects the yearly grade average in a positive, but negatively affects thenumber of failed courses.The university placement score affects the number ofunsuccessful courses negatively. While thegender affects positively the year-end grade average, it was not in ameaningful relationship with the number of failed courses. In addition, there is a strong positive relationshipbetween the placement score and preference order change in the university.

Bu araştırma;veri madenciliği kavramının temellerini ve uygulama alanlarını belirlemekamacıyla kuramsal bir inceleme olarak tasarlanmıştır. Bunun yanında, araştırma, ilahiyat fakültesine yerleşen öğrencilerin, fakülteye yerleştikten sonrakiakademik başarısına etki eden faktörlerin neler olduğunu, yerleşme puanlarınave çeşitli demografik değişkenlere göre açıklama amacını taşıyan örnek biruygulamayı da kapsamaktadır. Araştırma kapsamındaki yerleşen öğrencilerin, üniversite yerleşme puanları ile yerleştikleri fakültelerdeki başarı durumlarıarasındaki ilişki nicel araştırma yöntemlerinden veri madenciliği tekniğibelirlenmiştir. Bu uygulamada, 2017 yılında bir üniversiteye yerleşen ve halen ilahiyatlisans programlarının 2. Sınıflarında öğrenim gören 3775 öğrenciye ait veriörneklemi kullanılmıştır.Araştırma sonucunda, yılsonu not ortalaması ve başarısızolunan ders sayısı arasında negatif yönlü ve yüksek düzeyde bir ilişkibelirlenmiştir. Bunun yanında, yılsonu not ortalaması ve yaş arasında yüksekdüzeyde negatif ilişki belirlenmiştir.Öğrencinin üniversiteye yerleşme puanı, yılsonu notortalamasını olumlu yönde etkilerken, başarısız olunan ders sayısını olumsuzetkilemektedir. Üniversite yerleşme puanı, başarısız olunan ders sayısını olumsuz yönde etkilemektedir. Cinsiyet değişkeni yılsonu not ortalamasını olumlu bir şekilde etkilerken, başarısız olunan ders sayısı ile anlamlı bir ilişki içinde değildir. Bunun yanında, üniversiteye yerleşme puanı ile tercih sırası değişkeniarasında da pozitif yönlü oldukça güçlü bir anlamlı ilişki söz konusudur.
The Data Mining: Measurement of Academic Achievement in Faculty of Divinity by Data Mining
dinbil
Keywords: Data Mining; Academic Achievement; Divinity; Student; Veri Madenciliği; Akademik Başarı; İlahiyat; Öğrenci